Тепломассоперенос в подогреваемой снизу цилиндрической конвективной ячейке со свободной верхней границей при учете поверхностного натяжения - Андреева, О. Л.; Костиков, А. О.; Ткаченко, В. И. (НТУ "ХПИ", 2017)
У роботі наведені результати теоретичного дослідження процесу тепломасопереносу в циліндричній конвективній комірці з вільною верхньою границею при урахуванні поверхневого натягу. Запропоновано аналітичний вираз для обуреної вертикальної швидкості, який задовольняє умові рівності швидкості і її першії похіднії, які дорівнюють нулю на верхній і нижній межі шару (тверді граничні умови). Отриманий аналітичний вираз для обуреної температури задовольняє умові ідеальної теплопровідності на нижній границі, і умові теплопровідності на верхній границі, яка задається числом Біо. З граничної умови, обумовленої поверхневим натягом і умовами температуропровідності на верхній границі отриманого рівняння, що визначає взаємозв'язок сил плавучості і поверхневого натягу. З чисельного рішення цього рівняння отримані характерні хвильові числа циліндричної конвективної комірки, і визначена їх залежність від числа Біо.

The paper presents the results of a theoretical study of the process of heat and mass transfer in a cylindrical convective cell with a free upper boundary, taking into account the surface tension. An analytical expression is proposed for the perturbed vertical velocity, which satisfy the condition of equality of the velocity and its first derivative to zero at the upper and lower boundary of the layer (rigidboundary conditions). The obtained analytical expression for the perturbed temperature satisfies the condition of ideal thermal conductivity at the lower boundary, and the condition given by the Bio number of thermal conductivity at the upper boundary. From the boundary condition due to the surface tension, and the thermal diffusivity condition at the upper boundary, the equation is obtained. Determines the relationship between the forces of buoyancy and surface tension. From the numerical solution of this equation, the characteristic wave numbers of a cylindrical convective cell are obtained, and their dependence on the number of Bio is determined. The dependence of the Marngoni numbers on the wave number and the number of Bio is described analytically.
Heat and mass transfer in heated from below cylindrical convective cell with free upper boundary and taking in account of the surface tension
Keywords: поверхность жидкости; силиконовое масло; конвекция; эффект плавучести; коэффициент температурного расширения; конвективный массоперенос